Nation-State and its Body-Politics in Kashmir: Representation of State and its Structural violence in Shahnaz Bashir’s The Half Mother - Bandoghati, Somnath (International Journal of English Literature and Social Sciences (IJELS), 2019)
In modern day scenario, State has evolved into nation-state. The sense of belonging to a particular nation makes a particular territory to be governed by a single state. To normalize the governance nation-state strives to create nationalist subject which will do anything but question the sovereignty of the state over the territory. And state’s blanket monopoly over the armed forces works as a deterrent for the rebel population. It uses different form of tactics to both exert power and govern. This paper seeks to contextualize state violence in a contemporary award-winning Kashmiri novel The Half Mother: a novel with the critical perspectives of Foucault’s ‘bio-politic’ and ‘disciplinary society’ and also of Agamben’s concept of ‘bare life’. ‘Bio-politics’ is a mechanism through which ordinary human lives are managed and regulated by the existing power system. Agamben further develops the concept and contextualizes it in modern nation-state scenario. This paper closely examines the motifs and symbols deployed in the novel to portray the functioning of state-power during the armed insurgence against which the plot of the novel is set. The paper also argues that the novel is a conscious attempt on the part of the novelist to drive home a specific purpose i.e. building up of a discourse against state-occupation in the valley. Being true to the convention of ‘Resistance literature’ in The Half Mother also, the story is relegated to the periphery giving that discourse-formation the centre state, the characters remain flat and static and serve as puppet in the hands of its creator.